Purification and characterization of a novel antifungal protein with antiproliferation and anti-HIV-1 reverse transcriptase activities from Peganum harmala seeds - Ma, Xiaojin; Liu, Dongliang; Tang, Haishu; Wang, Yan; Wu, Ting; Li, Yang; Yang, Jie; Yang, Jianhua; Sun, Surong; Zhang, Fuchun (Acta biochimica et biophysica Sinica, 2013)
A novel antifungal protein, designated as PHP, was isolated from the seeds of Peganum harmala, by cationic exchange chromatography on Resource S column and gel filtration on Sephadex 75 10/300 GL column. PHP was found to form a homodimer of about 16 kDa. Isoelectric focusing polyacrylamide gel electrophoresis analysis showed that the isoelectric point of PHP was ∼8.4. The N-terminal 20-amino acid sequence of PHP, ITCPQVTQSLAPCVPYLISG, resembles the non-specific lipid transfer proteins in certain plants. PHP exhibited lipid-binding activity. Furthermore, PHP exerted antifungal activity against Alternaria alternate, Penicillium degitatum, Rhizopus stuolonifer, and Magnaporthe grisea, and its antifungal activity was stable in the temperature range 4-60°C, and in the pH range 4-10. It inhibited the mycelial growth in A. alternate, P. degitatum, R. stuolonifer, and M. grisea with 50% inhibitory concentration (IC(50)) of 1.5, 37.5, 8.44, and 12.19 μM, respectively. PHP was also able to inhibit the proliferation of esophagus carcinoma (Eca-109), cervical carcinoma (HeLa), gastric carcinoma (MGC-7), and melanoma (B16) cells with IC(50) of 0.7, 2.74, 3.13, and 1.47 μM, respectively. Moreover, PHP significantly inhibited HIV-1 reverse transcriptase (RT) with an IC(50) of 1.26 μM. It did not have hemagglutinating and antibacterial activities. In conclusion, a novel antifungal protein with antiproliferation and anti-HIV-1 RT activities was obtained from P. harmala seeds.